Nicola and the Viscount - Cabot, Meg (London Macmillan Children's Books, 2002)
Nicola always gets what she wants. Nicola Sparks, sixteen and an orphan, is ready to dive headlong into her first glittering London society season. She's also ready to dive headlong into the arms of handsome and debonair Lord Sebastian Bartholomew. Nicola's dream is a proposal from the viscount'a dream she's about to realize at last! So naturally, Nathaniel Sheridan's insinuations about her fiancE's flawed character annoy her mightily. But when Nicola's natural curiosity gets the best of her, she begins to piece together a few things for herself. To her great surprise, Nicola realizes she's had the wrong viscount all along ... but is it too late to make things right'
Keywords: England--London -- Great Britain